The system of the world - Stephenson, Neal (Stephenson, Neal. Baroque cycle, 2005)
In the wake of a power struggle between the throne-seeking Tories and Whigs in early eighteenth-century England, Daniel Waterhouse teams up with Isaac Newton to hunt down a shadowy group that uses time bombs to kill Natural Philosophers.